Carlos Castillo-Chavez: A century ahead - James Schatz (Mathematical Biosciences and Engineering)
When the opportunity to contribute a short essay about Dr. Carlos Castillo-Chavez presented itself in the context of this wonderful birthday celebration my immediate reaction was por supuesto que sí! Sixteen years ago, I travelled to Cornell University with my colleague at the National Security Agency (NSA) Barbara Deuink to meet Carlos and hear about his vision to expand the talent pool of mathematicians in our country. Our motivation was very simple. First of all, the Agency relies heavily on mathematicians to carry out its mission. If the U.S. mathematics community is not healthy, NSA is not healthy. Keeping our country safe requires a team of the sharpest minds in the nation to tackle amazing intellectual challenges on a daily basis. Second, the Agency cares deeply about diversity. Within the mathematical sciences, students with advanced degrees from the Chicano, Latino, Native American, and African-American communities are underrepresented. It was clear that addressing this issue would require visionary leadership and a long-term commitment. Carlos had the vision for a program that would provide promising undergraduates from minority communities with an opportunity to gain confidence and expertise through meaningful research experiences while sharing in the excitement of mathematical and scientific discovery. His commitment to the venture was unquestionable and that commitment has not waivered since the inception of the Mathematics and Theoretical Biology Institute (MTBI) in 1996.For more information please click the “Full Text” above.